PCW-01 WALLET: post COVID wallet / Muhammad Fuad Abdul Rahman - Abdul Rahman, Muhammad Fuad (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
After the Covid-19 pandemic, basic activities are back to normal with few restrictions and all citizen must follow standard operation procedures (SOP) that has been provided by the government. One of the activities is money transaction, even with the rise of digital payment it still comes with its drawbacks. Physical money transaction also comes with drawbacks such as the risk of being infected being higher. PCW-01 is a wallet that reduces the user being infected by the virus. The main function of this product is one hand operation paper money dispenser. Additional functions are refillable hand sanitiser spray, cards and coins compartments. This product used no electronic components, just simple mechanisms which can be easily replaced or repaired. The user can easily identify the moveable parts visibly and feel by using high colour contrast and hemisphere texture. The objectives of PCW-01 are (1) to dispense paper money using one hand only (2) to reduce the risk of being infected by the virus, (3) able to hold cards and coins in the wallet and (4) has a refillable sanitiser spray. An online survey with 20 questions is given to 31 participants virtually. This is used to acquire relevant information from the respondents regarding their behaviour before, during and after making money transactions physically, their view on digital payment and its drawback and their opinion on a wallet. Based on the online survey, it is shown that most of the respondent has a problem while using digital payment, the most frequent are slow Wi-Fi or data connection, the app unable or slow to respond and the phone or electronic device is unable to scan the QR code. Furthermore, their main payment method in a physical store and sometimes sanitize their hands after paying to the cashier. Hopefully, this product can reduce the risk of being infected while making physical money transactions in a physical store. PCW-01 may not replace the traditional wallet but in our current issue, it provides an alternative option to people.